Meningkatkan Hasil Belajar Siswa Kelas VI SDN 10 Sanggau Melalui Metode Penemuan Terbimbing Pada Materi Keliling Dan Luas Persegi Panjang - Veronika Emaliana Rosika Candra (LPPM Politeknik Pratama, 2023)
The problem in this research is how to improve the learning outcomes of CLASS VI students at SDN 10 SANGGAU through the guided discovery method on the material on the perimeter and area of ​​a rectangle. The purpose of this study was to describe how to improve the learning outcomes of CLASS VI students at SDN 10 SANGGAU through the guided discovery method on the perimeter and area of ​​a rectangle. The subjects of this study were 12 students of CLASS VI SDN 10 SANGGAU, academic year 2022-2023. The research design uses the Kemmis and Mc cycle models. Taggart. This research is a class action research (CAR) which was carried out in two cycles. Each cycle is carried out through a process of planning, action, observation or observation, and reflection. The data taken from this study are qualitative data and quantitative data. Data collection techniques used written tests, interviews, observations, field notes. Data analysis in this study was carried out by means of data reduction, data exposure, and data verification. Based on the results of the first cycle of research with the material around the rectangle obtained 100% mastery of classical learning with an average value of 8.83 and the results of the research cycle II with the material of the area of ​​the rectangle obtained 100% mastery of classical learning with an average value of 9.33. Thus it can be concluded that there is an increase in the learning outcomes of CLASS VI students at SDN 10 SANGGAU through the guided discovery method on the perimeter and area of ​​a rectangle.